Legal state – the guarantor of security of individuals and society in modern conditions (Journal of actual problems of jurisprudence, 2018)
This article reviews the analyses of theoretical propositions of legal state. The main focus is made to the principle of legal security. The conclusion about the need of increasing the responsibility of public authorities to the public is made. The recommendations aimed at improving of constitutional provisions governing protection and promotion of human rights are proposed.The principles of legal state are disclosed. The conclusion that the Republic of Kazakhstan is on the initial way of forming of legal state is made. The democratic states passed the protracted way on the formation of legal state. Accordingly, the Republic of Kazakhstan in article 1 of the Constitution has confirmed aspiration to become the legal state.Key words: legal state, constitutional norms, power, human rights, legal security.